Study on the Mechanical Relationship among the Backfilling Mining Support, Roof Rock Beam, and Gangue Filling Body in Comprehensive Mechanized Filling Mining Process - Zhimin Huang; Lei Zhang; Zhanguo Ma (Advances in Civil Engineering)
Based on the theory of elastic foundation beam, the mechanical model of the backfilling mining support-roof rock beam-gangue filling body under the condition of comprehensive mechanized filling mining is established. The foundation coefficient of each part is determined, and the subsidence of each part of roof rock beam is calculated. It is found that the initial filling height is the decisive factor to control the subsidence and migration stability of each part of the roof rock beam. Properly increasing the pushing force of backfilling-coal mining hydraulic support on the filling body can also effectively control the roof subsidence. The comprehensive mechanized filling mining process was studied by similar simulation experiments, it is found that the influence law of initial filling height on roof rock beam subsidence is the same as that of theoretical analysis, and the experimental measurement values and fitting function relationships are consistent with the theoretical calculation results.